Financial Planning for Education Funds Through Investment Options for Housewives in South Cicinde - Ery Rosmawati; Ujang Suherman; Thomas Nadeak (PT. Berkah Digital Teknologi, 2025)
Purpose of the study — The purpose of the study is To know How planning education fund finance for housewives in South Cicinde Village stairs via choice investment. Problems found​ that part big public there No own education fund preparation Because misunderstanding will management finance. Research method— Qualitative and quantitative approaches are used in this study. Through online surveys and in-depth interviews, Result— The results of research and data analysis show that the people of South Cicinde Village, especially housewives Already own planned education For their son. However, plan This is not supported by educational funding preparation​because 81.6% of the Respondent has No own savings term allocated length​ special for Education Fund. Choice investment For Educational funding planning chosen by respondents is Investment riches personal in the form of Gold and Wealth Real rice fields and buildings ( rent property ). Respondent No chose an investment as well as an Investment Commodity Because factor misunderstanding, as well as concern, will risk on investment which is rated very highly. Conclusion— Conclusion— Remembering planning education fund finance is very important For society, then start from Mother House stairs in the neighborhood the smallest must own knowledge will planning finance. Government village local or service related, Banking institutions and the Supervisory Agency (BI / OJK) routinely provide training as well as coaching to Mother House Ladder To add knowledge about planning and management finance.